2009
DOI: 10.3390/ijms10010174
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxins in Peanut Products in the Northeast Region of São Paulo, Brazil

Abstract: Abstract:The aim of the present study was to determine aflatoxin levels in peanut products traded in the Northeast region of São Paulo, Brazil. To this end, 240 samples of peanut products traded in the cities of Araras, Leme, Pirassununga and Porto Ferreira were collected from June 2006 to May 2007. The samples were analyzed for aflatoxins (AF) B 1 , B 2 , G 1 and G 2 by high performance liquid chromatography. Results showed 44.2% samples positive for AF at levels of 0.5 to 103.8 μg·kg -1 . Nine of the positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 12 publications
2
27
2
2
Order By: Relevance
“…Of the mycotoxins reported to contaminate peanut and peanut cake, aflatoxins have been studied by analytical methods dedicated to this class of compound (Awuah & Kpodo, 1996;Banu & Muthumary, 2008;Mutegi, Ngugi, Hendriks, & Jones, 2009;Oliveira, Goncalves, Rosim, & Fernandes, 2009;Younis & Malik, 2003). However, other toxins may be present in these commodities.…”
Section: Introductionmentioning
confidence: 99%
“…Of the mycotoxins reported to contaminate peanut and peanut cake, aflatoxins have been studied by analytical methods dedicated to this class of compound (Awuah & Kpodo, 1996;Banu & Muthumary, 2008;Mutegi, Ngugi, Hendriks, & Jones, 2009;Oliveira, Goncalves, Rosim, & Fernandes, 2009;Younis & Malik, 2003). However, other toxins may be present in these commodities.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin B 1 (AFB 1 ) is a secondary metabolite produced mainly by Aspergillus flavus and Aspergillus parasiticus, which is considered an unavoidable, naturally occurring contaminant of peanut and peanut oil. 1,2 Epidemiological studies and animal experiments showed that AFB 1 has strong genotoxic, carcinogenic and immunotoxic effects on humans and animals. 3 -5 Therefore many countries have legislated on the maximum levels of AFB 1 in foods to reduce its harm to humans.…”
Section: Introductionmentioning
confidence: 99%
“…This unusual AF occurrence ratio is not new. Matumba et al (2014) found that the concentration of AFG 1 was higher than that of AFB 1 in 47% of maize and groundnut samples, especially when high AF levels occurred; Oliveira, Goncalves, Rosim, and Fernandes (2009) reported similar concentrations of AFG 1 and AFB 1 in nuts of Brazilian origin. Matumba et al Table 2 Frequency of occurrence and concentration (mg kg À1 ) of aflatoxins (AFB 1 , AFB 2 , AFG 1 , AFG 2 ), ochratoxin (OTA), ciclopiazonic acid (CPA) and sterigmatocystin (STC) in fresh chestnut, dried chestnut and chestnut flour samples collected from retail outlets in Italy.…”
Section: Aspergillus Toxinsmentioning
confidence: 74%